2011
DOI: 10.1007/s00423-011-0783-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a tumor of increasing incidence and high mortality worldwide. Diagnosis of HCC is often difficult, especially at early stages of disease. Additionally, current treatment options are limited. HCC usually develops in an environment of chronic liver disease. The immune system has an important role in shaping this environment, especially in chronic viral hepatitis, the leading cause of HCC. However, the immune system also plays a role in natural immunity against HCC although this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 77 publications
1
19
0
1
Order By: Relevance
“…Immunotherapy strategies such as chimeric antigen receptor T cells and immune checkpoint blockade have been developed for decades in various human tumors, carrying high expectations based upon recent progress. As an "immune organ", liver shows unique antior pro-tumor responses during the progression of HCC [107]. Immune-modulators, tumor vaccines and adoptive immunotherapy proved effective in the clinical practice of HCC [108].…”
Section: Personalized Diagnosis and Therapymentioning
confidence: 99%
“…Immunotherapy strategies such as chimeric antigen receptor T cells and immune checkpoint blockade have been developed for decades in various human tumors, carrying high expectations based upon recent progress. As an "immune organ", liver shows unique antior pro-tumor responses during the progression of HCC [107]. Immune-modulators, tumor vaccines and adoptive immunotherapy proved effective in the clinical practice of HCC [108].…”
Section: Personalized Diagnosis and Therapymentioning
confidence: 99%
“…In HCC, several lines of evidence have suggest a positive role of immune system, e.g., by controlling hepatoma growth [7,[27][28][29]. Indeed, data from clinical investigations have revealed that HCC patients with an increased intratumoral accumulation of cytotoxic CD8 + T lymphocytes had a superior 5-year survival rate and a prolonged recurrence-free survival after liver resection [11,30].…”
Section: Immune Responses Against Hccmentioning
confidence: 99%
“…At present, several tumor-associated antigens (TAAs) of HCC have been identified, which has been recently introduced [7,33]. In brief, several shared tumor antigens could also be recognized as antigens targeted by cytotoxic CD8 + T cells in HCC, e.g., human telomerase-reverse transcriptase (hTERT) or NY-ESO-1.…”
Section: Immune Responses Against Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy has been explored in HCC for decades [4] and carries high expectations due to the recent progress in other malignancies such as melanoma. Different from other organs, liver shows its distinguished characteristics, such as an "immune organ", and patients with HCC present with unique anti-or pro-tumor responses during the development and progression of HCC [5] . Immunotherapy can be categorized into several types according to their distinct strategies.…”
Section: Introductionmentioning
confidence: 99%